Wear investigation of elastically similar sliding bodies material - Mazlan, Muharnad Muhaidi (Universiti Teknologi Petronas, 2011)
From the practical point of view to obtain the friction and wear characteristic of materials used in machinery, various types of wear testing machines have been developed and deployed. To obtain useful data for practical application, it is desirable that the investigation is carried out by a full scale wear testing apparatus having approximat.ely similar contact conditious. There are two parameters in the wear testing machines, such as configuration of contact surface and form of the relative motion between test specimens. Thus, in this report, the effect of unidirectional sliding friction in linear sliding direction between contacting pair and friction obtained test results are investigated. The reciprocating pin-on-flat experimental technique of similar specimen's material was modified to obtain the test results desired. The microscopic structures of the pin specimen were varied due to frictional and wear properties. Pressure distribution using selected formula during normal condition and the wear effect on the leading and trailing edge due to the movement of pin specimen were varied due to the load and number of cycles applied. Comparison between theoretical wear depth and experimental result been analyzed.